Sexual Behaviour of In-school Rural Adolescents in Ogun State, Nigeria (African Journal of Biomedical Research, 2019)
Adolescent sexual activities present health risks which can lead to negative reproductive health outcomes. This study assessed knowledge of, attitude to, sexual coercion experiences of, and confidence in adopting safer sex methods among in-school rural adolescents in Akute, Ogun State, Nigeria. This was a descriptive cross-sectional study (279 in-school adolescents ;108 males and 171 females). Knowledge attitude and practise questionnaire (Interviewer-administered) was used to assess socio-demographic characteristics, sexual coercion experiences and safer sex behaviour adopted. Frequencies was described and bivariate analysis between socio-demographic factors and adolescents’ sexual behaviour was calculated at p